BADANIA BIOGRAFICZNE JAKO ŹRÓDŁO REFLEKSJI NAD PROCESAMI NAUCZANIA/UCZENIA SIĘ JĘZYKÓW OBCYCH - Jaroszewska, Anna (Neofilolog, 2019)
If reflection is the necessary condition for successful development of all participants of the process of foreign language teaching and learning, as well as for the evolution of the scientific discipline, as we may now call glottodidactics, it is worth looking for all possible examples of it. In the light of this, the author of this article develops the thesis that appropriately designed studies based on biographies may provide rich and useful material for reflection on foreign language learning and teaching. The author also attempts to explain why biographical research is so rarely used in Polish glottodidactic studies and if this state of affairs could be changed.